Front Cover: Development of a High‐Pressure Reactor Based on Liquid‐Flow Pressurisation to Facilitate Enzymatic Hydroxylation of Gaseous Alkanes (ChemCatChem 19/2019). Issue 19 (19th September 2019) - Ariyasu, Shinya; Kodama, Yusaku; Kasai, Chie; Cong, Zhiqi; Stanfield, Joshua Kyle; Aiba, Yuichiro; Watanabe, Yoshihito; Shoji, Osami
Abstract : The Front Cover shows the concept of a novel high‐pressure reactor which compresses gaseous alkanes by pumping liquid forcibly (the person wearing a T‐shirt) into the reaction vessel without an exit (the trunk), and pressurizes up to 10 MPa. In their Communication, Yoshihito Watanabe, Osami Shoji, and co‐workers developed a novel high‐pressure reactor based on liquid‐flow pressurization using HPLC pump. Direct hydroxylation of gaseous alkanes by cytochrome P450BM3 with assistance of decoy molecules was drastically improved using this high‐pressure reactor. The TOF of propane‐hydroxylation reached 2200/min under 5 MPa of propane. Ethane hydroxylation was also greatly accelerated and the TOF reached 28/min. More information can be found in the Communication by Shinya Ariyasu, Yusaku Kodama, et al. on page 4709 in Issue 19, 2019 (DOI: 10.1002/cctc.201901323 ).